2009
DOI: 10.1007/s00125-009-1587-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential relationship between physical activity and progression to diabetes by glucose tolerance status: the Inter99 Study

Abstract: Aims/hypothesis The aim of the study was to analyse how strongly commuting and leisure-time physical activity affect progression to diabetes and to study whether this relationship is different in individuals with isolated impaired fasting glucose (i-IFG) and isolated impaired glucose tolerance (i-IGT). Methods We studied the incidence of diabetes in 4,031 individuals without diabetes at baseline who participated in the baseline and 5 year follow-up examinations of a population-based primary prevention study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
2
25
1
4
Order By: Relevance
“…Furthermore, similar to the AusDiab study23 and studies in Pima Indians,24 2-h PG levels were associated with the amount of physical activity, whereas FPG levels were not. Engberg et al showed that physical activity was associated with a lower progression to diabetes in patients with isolated IGT but not in patients with isolated IFG 25. It is suggested that the effect of physical activity on 2-h PG levels is mediated through an improvement in insulin sensitivity,26 which in turn increases the insulin-stimulated glucose uptake after the glucose load 14.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, similar to the AusDiab study23 and studies in Pima Indians,24 2-h PG levels were associated with the amount of physical activity, whereas FPG levels were not. Engberg et al showed that physical activity was associated with a lower progression to diabetes in patients with isolated IGT but not in patients with isolated IFG 25. It is suggested that the effect of physical activity on 2-h PG levels is mediated through an improvement in insulin sensitivity,26 which in turn increases the insulin-stimulated glucose uptake after the glucose load 14.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with i-IFG are known to have marked hepatic but not peripheral insulin resistance [12], suggesting that inulin may have a specific effect on hepatic insulin sensitivity. While our study was not powered to examine the effect of the intervention between the prediabetic subtypes, and our analysis was carried out post hoc, there is a growing body of evidence suggesting that the specific pathophysiology between the prediabetic states may mediate the effectiveness of interventions to prevent diabetes [34,35] . Based on our intriguing finding that inulin may specifically improve fasting insulin sensitivity, we would recommend an adequately powered study using a hyperinsulinaemic clamp with deuterated glucose to examine this more closely.…”
Section: Discussionmentioning
confidence: 99%
“…33,41 This study included assessment of hours of current physical activity status by a questionnaire. The questionnaire has been shown to be associated with biological risk factors for cardiovascular disease and with incident diabetes in the Inter99 Study, 42,43 but it has not been validated against objective measures of physical activity. Information about past physical activity would have been relevant, but it was not assessed in the Inter99 Study due to the expected recall and social desirability bias.…”
Section: Discussionmentioning
confidence: 99%